Pusat Pelatihan Usaha Mikro Kecil dan Menengah (UMKM) Berbasis Arsitektur Berkelanjutan - Setiawan, Ricky; Marwati, Marwati; Juddah, Safruddin (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting local economic growth; however, their development still requires training facilities that can improve production skills, managerial capacity, and business competitiveness. This study aims to design an MSME Business Training Center in Makassar City as a facility for developing new entrepreneurs, particularly in the craft, culinary, and fashion sectors. This study applies a descriptive-qualitative method through a literature review, a previous study, and field observation at the design site in Tanjung Merdeka Subdistrict, Tamalate District, Makassar City. The collected data were analyzed and synthesized into a design concept covering site selection, form transformation, site plan, circulation, parking area, building appearance, and interior arrangement. The design results show that the selected site is located in the Integrated Global Business Area and has good accessibility. A breakwater inspires the building form concept as a contextual response to Makassar’s coastal character. The application of sustainable architecture is reflected in land-use efficiency, green open-space design, natural lighting, ventilation, and circulation systems that support user comfort. Therefore, this design is expected to serve as a functional, contextual, and environmentally responsive MSME training facility